KETERBUKAAN INFORMASI PUBLIK TERHADAP PENGGUNAAN DANA DESA SEBAGAI UPAYA TRANSPARANSI PENGELOLAAN KEUANGAN DESA - Jhony K. Yoppy; Risno Mina; Firmansyah Fality (Fakultas Hukum, Universitas Samudra, 2021)
Once the importance of public information disclosure on the use of village funds is due to information on the use of village funds, will provide information about the use and use of village funds, will involve the community in managing village funds, will encourage the use of village funds based on the principles of good governance, will develop knowledge and will improve the quality of the use of village funds. The implementation of Public Information Openness regarding the use of village funds in Peley Village, South Totikum Subdistrict, Banggai Islands Regency has not been implemented because there is no Village Regulation on village public information disclosure, and the Village Information and Documentation Management Officer (Village PPID) has not been formed. However, to provide information about financial management, the Village Government is only limited to making billboards on the structure of the APBDesa, which is financed through the APBDesa